The Relationship of Social Media Usage to the Satisfaction and Practice of Friendship (Silaturahmi) among Students of Universitas Sumatera Utara - Feni Khairifa; Suwardi Lubis; Iskandar Zulkarnain (Budapest International Research and Critics University, 2019)
The study aims is to find out The Relationship of Social Media Usage to the Satisfaction and Practice of Friendship (Silaturahmi) among Students of Universitas Sumatera Utara. This research is conducted at Universitas Sumatera Utara, Dr. Mansur Street, Padang Bulan, Medan. The result shows that there is a relationship between the use of social media and social satisfaction among students of the University of North Sumatra. The form of relationships is low, but certain relationships. In addition, the relationship between the two variables is positive, which means more and more use of social media, the satisfaction of friendship among students of the University of North Sumatra will also be higher. This is because, there is a positive side to social media. A variety of features are offered, making it easier for users to communicate. Distance, space and time are no longer a barrier to stay in touch (communication).